2021
DOI: 10.1001/jama.2021.14846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pulmonary Embolism Diagnostic Strategy on Clinical Outcomes in Patients Hospitalized for COPD Exacerbation

Abstract: Key PointsQuestionDoes an active search for pulmonary embolism (PE) improve outcomes in patients hospitalized for exacerbations of chronic obstructive pulmonary disease (COPD)?FindingsThis multicenter randomized clinical trial included 746 patients who required hospitalization for exacerbation of COPD and were randomized to receive usual care plus an active strategy for diagnosing PE or usual care alone. The primary outcome (a composite of nonfatal symptomatic venous thromboembolism, readmission for COPD, or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…This study might have practical implications. The SLICE trial showed that an active diagnostic strategy for PE is not beneficial among patients hospitalized for an exacerbation of COPD [ 11 ]. However, D-dimer is often used in daily practice as a screening test in patients admitted to the Emergency Departments with chest symptoms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study might have practical implications. The SLICE trial showed that an active diagnostic strategy for PE is not beneficial among patients hospitalized for an exacerbation of COPD [ 11 ]. However, D-dimer is often used in daily practice as a screening test in patients admitted to the Emergency Departments with chest symptoms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…SLICE was a multicenter, open-label, randomized, clinical trial aimed at evaluating whether an active search for PE might improve clinical outcomes in patients with exacerbations of COPD who required hospital admission. The rationale, design and main results of the SLICE study were described previously [ 11 , 12 ]. The trial was conducted in 18 academic hospitals across Spain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study published by Jiménez et al assessed whether active research of pulmonary embolism by D-Dimer dosing and computed pulmonary angiogram in hospitalized patients for COPD exacerbations is followed by a reduction in the composite risk of nonfatal symptomatic venous thromboembolism (VTE), readmission for COPD, or death within 90 days. 40 In the analysis were included 370 actively investigated cases, compared to 367 cases that received the usual care. Standard therapy included administration of oxygen, bronchodilators, antibiotics and prophylactic thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…The SLICE trial 40 revealed that anticoagulant treatment in hospitalized patients for exacerbation of COPD, actively investigated for pulmonary embolism, does not bring additional benefits to prophylactic therapy. This finding substantially supports the arguments regarding the administration of prophylactic treatment to patients with COPD, as recommended by the Global Initiative for Chronic Obstructive Lung Disease in patients with severe COPD.…”
Section: Introductionmentioning
confidence: 99%